Eksplorasi Etnomatematika Pada Batik Kayu Krebet Bantul - Ahmad Abdullah; Amin Rahmawati (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Batik is a world cultural heritage owned by Indonesia. In Krebet village, Sendangsari, Pajangan, Bantul, Batik is painted on wood or known as wooden batik. This wooden batik decorates household appliances. Wooden batik of Krebet has not been maximally utilized in learning science, especially mathematics. Even though there are many mathematical concepts contained in it. This study aims to explore mathematical concepts in wooden batik, especially geometric materials. In this study, researchers used exploratory research with an ethnographic approach. The instrument in this research is the human instrument, where the researcher is directly related to the research and acts as a data collector through observation, library data collection, documentation, and interviews. Data analysis techniques are carried out by domain and taxonomic analysis. The results showed that wooden batik of Krebet contains geometric concepts including the concepts of lines and angles, rectangles and triangles, circles, solid geometry, congruence, and geometric transformation